Molecular detection of lumpy skin disease virus in cattle by polymerase chain reaction in Iraq: Khitam Mahdi Mhemid and Ibtesam Qasim Hassan - Mhemid, Khitam Mahdi (The Iraqi Journal of Veterinary Medicine, 2016)
This study is conducted to detect lumpy skin disease virus in Babylon, Al-Qadysia and Al-Muthana governorate during autumn 2014 using conventional polymerase chain reaction. A total of 150 specimens: 50 whole blood samples, 50 skin nodular biopsies and 50 tick samples were collected from infected animals of different breeds, genders and ages during lumpy skin disease outbreak. The results revealed that 104 cases (69.33%) were positive for lumpy skin disease virus by using polymerase chain reaction, with significant (P<0.05) differences between positive and negative cases. Out of 50 blood samples, 22 cases (44%) were positive for lumpy skin disease virus. The nodular skin samples collected from slaughtered animals showed 36 positive cases (72%), whereas 46 tick samples (92%) were positive for the disease, with significant (P<0.05) difference among them. According to gender, the finding showed significant results of lumpy skin disease in females (78.78%). It was recorded that higher percentage of positive cases was found in Friesian cattle (100%), crossbreed (73.58%) while native breed was (50.76%) with significant (P<0.05) difference among them. Regarding age groups, the results showed that all ages were susceptible to lumpy skin disease and significantly not different.